2011
DOI: 10.1016/j.jaci.2011.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of transmembrane activator and calcium-modulating cyclophilin ligand interactor (TACI) mutations associated with common variable immunodeficiency

Abstract: Some, but not all, TACI mutations found in CVID impair TACI function and may potentially contribute to B cell dysfunction in heterozygotes via haploinsufficiency. Keywords TACI; common variable immunodeficiency; APRIL; BAFF; BLyS To the EditorMutations in TNFRSF13B, the gene encoding for the transmembrane activator, calciummodulator and cyclophilin ligand interactor (TACI), have been identified in 5-10% of patients with CVID 1, 2 . The most common TACI variants in CVID are C104R, in the ligand binding cysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 10 publications
(17 reference statements)
3
32
0
Order By: Relevance
“…The I87N mutation is located in the second CRD and is shown to result in residual BAFF binding, which increased with increasing concentrations of ligand, suggesting a decreased ligand-binding affinity of this mutant. 22 Signaling through TACI requires a trimerization of the receptor. [23][24][25] It is thus possible that inclusion of even one mutant receptor might affect the signaling by the complex.…”
Section: Discussionmentioning
confidence: 99%
“…The I87N mutation is located in the second CRD and is shown to result in residual BAFF binding, which increased with increasing concentrations of ligand, suggesting a decreased ligand-binding affinity of this mutant. 22 Signaling through TACI requires a trimerization of the receptor. [23][24][25] It is thus possible that inclusion of even one mutant receptor might affect the signaling by the complex.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the most dramatic difference between CVID and other typical primary immunodeficiencies concerns the penetrance of disease associated with allelic variants of TACI and other receptors. In contrast to full penetrance of the null mutations BTK or CD40, which cause X-linked agammaglobulinemia, or hyper-IgM syndrome, respectively, allelic variants of TACI, such as C104R and A181E, which impair TACI function even in the heterozygous state (16), usually exhibit no clinically significant defects in immunity (17). Thus, Salzer et al (18) found heterozygous C104R or A181E TACI variants in 6.9% of subjects with CVID but also in 2% of 675 normal adults.…”
Section: Introductionmentioning
confidence: 98%
“…Neither variant interfered with oligomerization with wildtype TACI molecules nor NF B activation was unaffected in 293T cells with wildtype and mutant TACI [26]. Dominant-negative interference of the variants with wildtype TACI is therefore improbable, but haploinsufficiency was not completely excluded.…”
Section: Introductionmentioning
confidence: 95%
“…Initially, the deficiency was attributed to a dominant-negative interference of the C104R polymorphism in trimeric complexes with TACI wildtype [21]. Subsequent reports; however, suggest haploinsufficiency of the TACI allele [25][26][27].…”
Section: Introductionmentioning
confidence: 99%